2002
DOI: 10.1007/s005350200133
|View full text |Cite
|
Sign up to set email alerts
|

Pit pattern and three-dimensional configuration of isolated crypts from the patients with colorectal neoplasm

Abstract: Evaluation of the three-dimensional configuration revealed that when the pit patterns, of each isolated crypt differed, their three-dimensional configurations also differed. Recognition of the differences in the three-dimensional configuration should contribute toward both an understanding of pit-pattern diagnosis and the further development of the endoscopic diagnosis of various colorectal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The orifi ces of the colonic gland can be elegantly visualized by SEM, but it is not possible to evaluate the deeper part of the glands without crypt isolation. Tamura et al 11 investigated and reported the three-dimensional structure of gland ducts corresponding to different pit patterns by using duct isolation.…”
Section: And Subsequentmentioning
confidence: 99%
See 3 more Smart Citations
“…The orifi ces of the colonic gland can be elegantly visualized by SEM, but it is not possible to evaluate the deeper part of the glands without crypt isolation. Tamura et al 11 investigated and reported the three-dimensional structure of gland ducts corresponding to different pit patterns by using duct isolation.…”
Section: And Subsequentmentioning
confidence: 99%
“…21,22 The fi ndings of pit pattern studies have led to questions from endoscopic physicians regarding the relationship between the pits and the three-dimensional shape of the gland ducts. Tamura et al 11 examined the threedimensional structure of pit patterns using SEM. 11 This method, which involves much higher magnifi cation than is possible with endoscopy, is very useful for the investigation of tumor gland morphology.…”
Section: And Subsequentmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, in the type-IIIl pit pattern, the structural differences between superficial-type and protruded-type tumor are still obscure. We investigated isolated crypts, using an HCl-digestion method, 5 in LST nongranular type 1 (LST-NG) superficial tumors and Background.…”
Section: Introductionmentioning
confidence: 99%